Strategi Peningkatan Prestasi Kerja Aparatur Sipil Negara Badan Kepegawaian Dan Diklat Daerah Kabupaten Enrekang - Bahar, Nur Azmi; Abdi, Abdi; Riskasari, Riskasari (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
This study purposed a strategy to improve the work performance of civil servants and state education and training institutions in Enrekang Regency.This study used qualitative research with its type was descriptive. The number of informants in this study were 8 people using purposive sampling techniques. Data collection techniques used observation, interviews and documentation. The results showed that the strategy of increasing the work performance of the state civil service staff and the regional training and training district of Enrekang was effective. This could be seen from the quantity aspect seen from the work programs that had been planned in each sub-sector, all of which had been realized effectively, as evidenced by the level of percentage of work that was more dominant above 90%, the aspect of timeliness seen from the number of work programs that had been planned to be implemented in on time, aspects of effectiveness the cost of all work program in each sub-sector was above 60% and even reached 100%. But in the aspect of quality and oversight had not been effective, although there was an increase in performance in the aspect of quality but employee discipline was still low because it only of supervision requiredvmore routine supervision.